(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
The following article deals with atmospheric boundaries in landscapes. The first part focuses on their change, the situational shifting of atmospheric boundaries – their fading in and out, their temporality on the one hand, and their permanence on the other. The initial focus will be on landscapes in general, and on their boundaries that include atmospheres as boundary phenomena. Special attention (in a phenomenological sense) is given to the ‘psychoscape’ in which emotional border-experience is formed. The second part is dedicated to a current topic of political atmospherology. It will explore the atmospheric borders of war, which, for their part, unfold in actual space, but at the same time, also dispose of the atmospheric border experience. Thus, the article presents an analysis and description of the varieties of borders and boundaries that war transforms or creates. Russia’s aggression against Ukraine is used as an example.